Mixed Ligand Complexes of Alkali Metal salts of Some Organic Acids with Picolinic Acid - Prakash, D.; Sinha, K.B.; Kumar, B.; K. Gupta, Anu (Asian Journal of Chemistry, 2010)
The mixed ligand complexes of the general formula ML·HL' where M = Li, Na or K, L = deprotonated 2,4-dinitrophenol, 2,4,6- trinitrophenol, o-nitronaphthol, 2,4-dinitronaphthol and HL' = picolinic acid, have been synthesised and characterised by physical methods. IR spectral data show that hydrogen bonding in these complexes are dominant factors for their stability.